PERSEPSI MASYARAKAT TERHADAP KEMUNGKINAN PENGEMBANGAN LUMBUNG DESA DI KABUPATEN TABANAN, BALI - BUDIASA, I WAYAN; USTRIYANA, I NYOMAN GEDE; ANGGRENI, IGAA LIES (SOCA: Jurnal Sosial Ekonomi Pertanian, 2016)
Lumbung desa is a food institution in the village level that supports the food security improvement program (Desa Mandiri Pangan ) in rural area. This study aims to assess the social perception toward development of lumbung desa in Tabanan Regency. Survey method was used to collect primary data from 60 households through non proportional random sampling in Riang Gede Village, Penebel District and Belimbing Village, Pupuan District. By using descriptive analysis, it was found that the social perception toward lumbung desa development in study area fell into good category. It means that, the lumbung desa in the study area was required. Therefore, it is suggested that the local government should support the lumbung desa development progam.
Keywords: lumbung desa food security; perception